Self Oscillating Mixer with Dielectric Resonator for Low Noise Block Application - Achmad Munir; Endon Bharata (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
In this paper, the development of a self oscillating mixer (SOM) as part of a low noise block (LNB) for a satellite television receiver is investigated numerically and experimentally. In contrast to other mixers, the developed SOM requires no separate local oscillator as it generates own local oscillator signal. The SOM is developed using a monolithic microwave integrated circuit (MMIC) comprised of two bipolar transistors coupled as a Darlington pair and a dielectric resonator to establish a local oscillator signal. The SOM is designed to oscillate at 3.62GHz driven from 50W signal generator. The prototype of SOM is fabricated on a dielectric substrate of glass-reinforced hydrocarbon/ceramic lamination (RO4350B) board which has a thickness of 0.762mm and relative permittivity of 3.66. The prototype is then characterized experimentally and exhibits a conversion gain of 8dB with the input and output voltage standing wave ratio (VSWR) less than 2 across the 2520MHz to 2670MHz operating frequency band.